Comparative Syntactic Analysis of Basic Sentence Structures in Tausug and English: Implications for Language Teaching and Learning - Salasain, Abdel Ajim M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study investigates the basic sentence patterns of Tausug (Bahasa Sug) and English, exploring their structural similarities and differences through a descriptive research design. The research involved 80 native Tausug speakers with advanced English proficiency from Jolo, Sulu, Philippines, and used Paul Roberts's (1956) seven basic sentence patterns as an analytical framework. The study addressed three primary research questions: (1) the contemporary significance of Tausug language studies, (2) the integration of Tausug jargon and idiomatic expressions in language standardization efforts, and (3) the syntactic variations between English and Tausug grammatical structures. Data were collected using an 82-item survey instrument examining Tausug jargon, idiomatic expressions, basic sentence patterns, and sociolinguistic factors such as Tausug's role as a regional lingua franca, its influence on neighboring ethnolinguistic groups, and its significance in governance and education. Statistical analysis employed descriptive methods and weighted means. The results revealed a significant language shift among younger Tausug speakers, leading to a decline in formal Tausug proficiency, despite its status as the lingua franca of the Sulu Archipelago. Although there are structural parallels between Tausug and English basic sentence patterns, notable syntactic variations were identified, particularly in word order and sentence structure. These findings suggest that while Tausug retains some structural similarities to English, the syntactic differences could impact second language acquisition, particularly for those learning English as a second language. Moreover, the decline in Tausug proficiency underscores the need for efforts to preserve and standardize the language, integrating its unique jargon and idiomatic expressions into educational and governance contexts to promote its continued use and development.